Analysis of Rotational Speed Variation of Umbi Teki Skin Peeling Machine in Chips Making Process - Siti Nur Fatimah; Tri mulyanto (Journal of Applied Science and Advanced Engineering, 2023)
The Umbi teki skin peeling machine is a machine used to assist in the process of making chips. Umbi teki, which will be processed into chips, will go through several processing processes, such as soaking the material with clean water first and then peeling the fiber and skin until it is clean, then roasting until the texture of the seeds starts to soften and then pounded using a hammer, after which it is dried in the sun until it is scorched. One of these production processes is carried out using this peeling machine to peel the skin of the Umbi teki. Factors affecting peeling include engine rotation speed (rpm), while some researchers state that the best average rotation speed on a peeling machine is 250-500 rpm. This study aims to determine the effect of engine rotation speed on stripping results and find the best rotation speed on an Umbi teki peeling machine with a load of 121 grams/minute. The method used in this research is an experimental study conducted with ten rotation speed variations. Data were analyzed using ANOVA to determine the best variation treatment. Results show that using engine rotation speed variables affects the average difference in skin stripping. The best engine rotation speed of 626 rpm produces the best percentage of stripping results, with a value for TB (Well Peeled) and TS (Not Perfectly Peeled) being 87.3%  and 9.3%, respectively.